Effect of MgCI2 and CaCI2 on the Bubble Point of Mixed- Solvents (Toluene-Isopropyl Alcohol-H20 System) - Nathaniel P. Dugos; Noel P. Cabigon; Yolanda P. Brondial (Department of Chemical Engineering, Universitas Gadjah Mada, 2006)
This study investigated the effect of CaCl2 and MgCI2,both alkaline earth metal salts on the boiling points of a mixed-solvent system composed of toluene, isopropyl alcohol and water. The effect of the concentration of the salt on the boiling point of this ternary system was also examined. Results showed that mixed- solvents added with CaCl2 boil at higher temperatures than those with MgCl2even though the latter salt is higher in molal concentration. This proves that MgCI2, which has a smaller ionic radius than CaCl2 is more effective in reducing the molecular affinity to polar and associating solvents (water and isopropyl alcohol) than to the non-polar solvent (toluene). The mixed- solvent system added with MgCl2 registered higher boiling point deviation than those with CaCI2, though both showed positive deviations. Based on the results, either of the two salts can be an effective mass separating agent. However it is shown that MgCl2is better than CaCl2 because the solutions with MgCI2 generally exhibited lower boiling points. Though the difference in temperature deviations of the two salts is statistically not significant, a difference in temperature of one degree is economically significant considering the cost of energy.